Game Plan For Life - Wooden, John. (New York Audible studios, 2009)
After eight books, many of them best sellers, A Game Plan for Life is the one closest to John Wooden's heart: a moving and inspirational guide to the power of mentorship. The first half focuses on the people who helped foster the values that carried Wooden through an incredibly successful and famously principled career, including his college coach, his wife, Abraham Lincoln, and Mother Teresa. The second half is built around interviews with some of the many people he mentored over the years, including Kareem Abdul- Jabbar, Bill Walton, fellow coaches, family members, and even a middle school coach in Canada.
Keywords: Personal development